2014
DOI: 10.1039/c3ra47659f
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of nanostructured α and δ MnO2 for lithium oxygen battery application

Abstract: a-and d-MnO 2 nanomaterials with different morphology like urchins and flowers are successfully synthesized by a low temperature hydrothermal synthesis. The prepared nanostructures were applied as electrocatalysts for air cathodes in Li air batteries. The synthesized materials possess high electrocatalytic activity and the MnO 2 catalysed electrodes doubled the initial cycling capacity of the Li air cells without any catalysts. We also observed reduced over potential and upon cycling with limited capacity, a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Among them, manganese‐based oxides are one of the most promising and favorable candidates, on account of their high ORR and OER catalytic activities and abundant reserves . Notably, Bruce and co‐workers systematically compared the catalytic performance of various manganese oxides including α‐, β‐, γ‐, λ‐MnO 2 , Mn 2 O 3 , and Mn 3 O 4 , and concluded that α‐MnO 2 is the most effective catalyst among them as the electrocatalyst for Li–O 2 batteries, delivering a capacity of 3000 mA h g −1 . This mainly originates from the large α‐MnO 2 (2 × 2) tunnel structure that is capable of accommodating more reversible storage and remove of lithium oxides (Li x O y ) and facilitating the rapid diffusion of O 2 2− and Li + , thus making it to be an highly effective electrocatalyst .…”
mentioning
confidence: 99%
“…Among them, manganese‐based oxides are one of the most promising and favorable candidates, on account of their high ORR and OER catalytic activities and abundant reserves . Notably, Bruce and co‐workers systematically compared the catalytic performance of various manganese oxides including α‐, β‐, γ‐, λ‐MnO 2 , Mn 2 O 3 , and Mn 3 O 4 , and concluded that α‐MnO 2 is the most effective catalyst among them as the electrocatalyst for Li–O 2 batteries, delivering a capacity of 3000 mA h g −1 . This mainly originates from the large α‐MnO 2 (2 × 2) tunnel structure that is capable of accommodating more reversible storage and remove of lithium oxides (Li x O y ) and facilitating the rapid diffusion of O 2 2− and Li + , thus making it to be an highly effective electrocatalyst .…”
mentioning
confidence: 99%
“…Subsequently, Zahoor et al made a comparative study on two different crystallographic MnO 2 with different morphologies, i.e., sea urchin shaped α‐MnO 2 and flower shaped δ‐MnO 2 . The result revealed that urchin shaped α‐MnO 2 catalyzed Li–O 2 battery delivered a higher discharge capacity and better cyclic stability than flower shaped δ‐MnO 2 catalyzed one . Based on the above‐reported results, the maximization of the electrochemical activity for nanostructured α‐MnO 2 can be attributed to the improvement of electron transfer and the increase of high exposure active sites of α‐MnO 2 nanostructure when acted as cathodic catalyst in Li–O 2 battery.…”
Section: The Types Of Manganese‐based Oxides For Li–o2 Battery Cathodmentioning
confidence: 76%
“…Bruce and co‐workers first proved that, comparing with other crystal structures of MnO 2 (including β‐MnO 2 , γ‐MnO 2 , λ‐MnO 2 , Mn 2 O 3, and Mn 3 O 4 ), α‐MnO 2 nanowires can offer a high initial discharge capacity up to 3000 mAh g −1 and can obviously reduce the charge overpotential . Up to now, a variety of α‐MnO 2 nanostructures, such as nanowires, nanorods, nanotubes, hollow clews, nanospheres, and sea urchin‐like morphology, have been synthesized and used as cathodic electrocatalysts of Li–O 2 batteries, which displayed remarkable catalytic activity, moreover, effectually improved the performance of Li–O 2 batteries. For example, Kalubarme et al reported that α‐MnO 2 nanorods with an average diameter of 25 nm delivered a higher discharge capacity than β‐MnO 2 nanoneedles and α‐MnO 2 nanorods with a larger diameter of 40 nm .…”
Section: The Types Of Manganese‐based Oxides For Li–o2 Battery Cathodmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] Hierarchical structures were obtained using a high KMnO 4 concentration at relatively low temperature and short time since high KMnO 4 concentration promoted the generation of nanorods and subsequent aggregation, whereas higher temperature and longer time destroyed the 3D structure during the violently boiling reaction. [23][24][25][26][27] Fine control of synthesis temperature, time and ion concentrations is the key factor for the successful synthesis of hierarchical assemblies, since these parameters have significant effects on nucleation and growth of crystal materials. 22 Perfect dandelion-like and dendritic nanoparticles composed of uniform OMS-2 nanoneedles and tetragonal prism nanorods, respectively, were obtained using K 2 Cr 2 O 7 which was hypertoxic, 10 indicating that a change of oxidant was necessary.…”
Section: Introductionmentioning
confidence: 99%